Motivations for Healthy Lifestyle in Railroad Employees - Ostan, Iztok; Poljšak, Borut; Podovšovnik Axelsson, Eva (Promet - Traffic&Transportation, 2012)
The aim of the paper is to present the results of a survey of railroad employees’ motivation for a healthy lifestyle. For this purpose a specific questionnaire was developed. The study was performed on 245 Slovene railroad workers (168 of them blue-collar ones). The great majority (66.9%) were found to be overweight or obese (BMI 25 or more), with no significant difference between blue- and white-collar workers. The great majority of them were in general aware of having unhealthy nutrition and an unhealthy lifestyle. Most of the employees felt the need to improve (at least in part) their nutrition (74.7%) and lifestyle (78.0%); the majority (67.8%) also declared that they could adopt a healthier lifestyle despite the constraints of everyday life and work conditions; however, 57.6% said that they had been already putting considerable effort into a healthier nutrition and lifestyle. Thus the effort needed to overcome constraints toward a healthier lifestyle seems to be the key problem: the majority (54.3%) would rather choose walking than running or other intensive forms of exercise; they are not ready to do it for more than one hour per day (60%), and they are not ready to give up permanently food that they like and that is considered unhealthy. The differences in motivations for a healthy lifestyle between blue- and white-collar workers were not significant at the 0.05 level. Further research in this field is needed; however, it seems that the methods of efficient marginal modifications of lifestyle are required. KEYWORDS human resources management, railroad, blue-collar workers, white-collar workers, healthy lifestyle, motivations